Major determinant factors of pediatric COVID-19 severity; a single center study - Heba A. Ali (SpringerOpen, 2023)
Abstract Background According to several recently published studies, pediatric Corona virus infection is mostly mild. However, a severe COVID-19 illness could occur in children, resulting in grave outcomes. Unfortunately, the data regarding the major determinants of disease progression in the pediatric population is still limited. Here, we aimed to identify the most significant risk factors associated with severe COVID-19 infection in children to predict the patients at elevated risk for serious illness. Results This single-center, retrospective study enrolled eighty hospitalized children and adolescents under the age of 18 years with coronavirus type 2 infections, who were divided according to the level of clinical severity into severe and non-severe groups. Epidemiological data, clinical features, radiological findings, laboratory test results, and disease outcomes of the studied patients were collected and analyzed to demonstrate their relation to disease severity. Patients with severe illness tend to have more respiratory symptoms (97.8% vs. 79.4%, p = 0.007), cardiac affection (23 (50.0%) vs. 5 (14.7%), p = 0.001, and neurological involvement (13 (28.1%) vs. 1 (2.9%), p = 0.003). Furthermore, abnormal radiological findings and higher radiological scores were significantly more common among patients with severe disease compared to non-severe cases (p = 0.037, 0.013). In multivariable analysis, clinical scoring, abnormal coagulation function, and ICU admission were the most significant parameters for forecasting severe illness. Conclusions We identified the most remarkable parameters involved in the progression of severe disease in Egyptian children with COVID-19 infection, which may be implemented in anticipation of susceptible children for earlier prompt management and a better prognosis.